Optimizing BUMDes in Improving the Village Economy through Creative Ideas - Ali, Helmi; Setrojoyo, Sudarmo Muhammad; Masela, Mesak Yandri; Pratiwi, Ratih; Nur, Muhammad; Nazmah, Nazmah (LP2M INSURI Ponorogo, 2023)
Many people are experiencing economic difficulties due to decreased income and have lost their jobs, so they no longer have the income to meet their financial needs in the Koto Ranah Traditional Village, Koto Besar Dharmasraya. So, in this case, BUMDes is needed to mobilize village potential and assist in poverty alleviation efforts. The purpose of this service activity is to optimize seven Business Units, namely public service units, leasing units, intermediary units, trading units, finance and loan units, joint business units, and contractor or developer unions in the Koto Ranah Traditional Village to deal with the economic crisis that occurred. The results of the dedication stated that the Trading Unit of the Koto Ranah Sakti BUMDes made a breakthrough by helping the economy through the sale of LPG Gas and Mineral Water at affordable prices, where LPG Gas and Mineral Water are important basic needs in every household that are needed and used every day. With the KKN program, by empowering BUMDes, Koto Ranah Sakti can continue to manage the community's economy amid a pandemic, not so that BUMDes can develop more advanced.